2008
DOI: 10.1007/s11627-008-9178-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plant origin on propagation capacity and alkaloid biosynthesis during long-term in vitro cultivation of Leucojum aestivum L.

Abstract: The investigation deals with in vitro clonal propagation of L. aestivum L. (Summer Snowflake), a threatened Amaryllidaceae plant species in Bulgaria used in the pharmaceutical industry as raw material for production of galanthamine-based medicines. Plants of known origin and with different alkaloid profile were taken from the living collection of the Institute of Botany, Sofia. Bulbs were used to initiate in vitro cultures and 24 clones were multiplied. The influence of the clone origin on the propagation coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Galanthamine levels of some of the in vitro obtained clones was as high as galantamine levels of commercially important representative of Bulgarian L. aestivum populations. Five clones: four galanthamine-type and one lycorine-type were selected as promising for further investigations [140].…”
Section: In Vitro Cultures and Application Of Biotechnology In Gentiamentioning
confidence: 99%
“…Galanthamine levels of some of the in vitro obtained clones was as high as galantamine levels of commercially important representative of Bulgarian L. aestivum populations. Five clones: four galanthamine-type and one lycorine-type were selected as promising for further investigations [140].…”
Section: In Vitro Cultures and Application Of Biotechnology In Gentiamentioning
confidence: 99%
“…, galanthamine content in L. aestivum directly regenerated bulblets was 10 times greater than in L. aestivum callus‐derived shoots (over 1 mg/g DW vs. 0.1 to 0.2 mg/g DW). According to the same team, genotype is another crucially important factor for the biosynthetic capacity of in vitro cultures . It defines, inter alia, the dominant alkaloid biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrates that a micropropagation system, not involving the production of embryogenic calli, can also be established for this species. Besides our report, several studies reported the production of L. aestivum tissue cultures [7,26], but none of them involved the assay of antioxidant capacities (see below). All cultures showed high shoot / whole plant and (except L. aestivum) high bulblet regeneration frequencies (Tab.…”
Section: Discussionmentioning
confidence: 94%